The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1213/ane.0000000000002727
|View full text |Cite
|
Sign up to set email alerts
|

Misaligned Feeding May Aggravate Pain by Disruption of Sleep–Awake Rhythm

Abstract: Misaligned diet might aggravate pain sensitivity through the disruption of the sleep-awake cycle, which could be recovered by Mel. NR2B-CaMKII-CREB may participate in the disruption of sleep-awake rhythm-mediated pain aggravation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“… 44 In a study of mice, exposure to sustained misaligned-time feeding led to an altered rest-activity rhythm and greater sensitivity to pain, with recovery after the administration of melatonin. 45 It is also postulated that painful conditions would occur with a certain rhythm, probably due to the homeostatic sleep drive and circadian rhythms modulating pain neural pathways. 46 …”
Section: Discussionmentioning
confidence: 99%
“… 44 In a study of mice, exposure to sustained misaligned-time feeding led to an altered rest-activity rhythm and greater sensitivity to pain, with recovery after the administration of melatonin. 45 It is also postulated that painful conditions would occur with a certain rhythm, probably due to the homeostatic sleep drive and circadian rhythms modulating pain neural pathways. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Another study similarly reported alterations in mechanical withdrawal thresholds in a simulated jet lag paradigm ( Das et al, 2018 ). A final study examined the effect of mistimed eating on mechanical withdrawal thresholds in a mouse model of neuropathic pain ( Xu et al, 2018 ). Food consumption restricted to the inactive phase exaggerated mechanical allodynia in male mice with chronic constriction injury ( Xu et al, 2018 ).…”
Section: Circadian Rhythm Disruption Pain and Opioids: A Feedback Loopmentioning
confidence: 99%
“…96,97 Misaligned diet and sleep deprivation during the peri-CCI surgery and post-CCI distinctly decrease the paw withdrawal mechanical threshold, whereas melatonin pretreatment ameliorates the hypersensitivity and reverses the disturbed sleep rhythm. 94,98 In other neuropathic pain models, such as cuff implantation, valproic acid, and paclitaxel, melatonin ameliorates mechanical and thermal allodynia by preventing the increases in NO levels, down-regulating c-fos, and increasing C-fiber activity. 17,99,100 Growing evidence suggests that melatonin administration may reverse the nociceptive threshold in spinal nerve ligation (SNL) rodents.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…61 The up-regulation of NMDA receptor subtype 2B (NR2B), Ca 2+ /calmodulin-dependent protein kinase II (CaMKII), and cyclic adenosine monophosphate-response element-binding protein (CREB) is induced by nerve injury, which can be recovered by melatonin pretreatment. 98 Furthermore, melatonin administration attenuates the NR1 expression and reduces NMDA-induced currents in dorsal horn neurons in rodents with unilateral temporomandibular joint (TMJ) inflammation in a dose-dependent manner. 134 The treatment of neuropathic pain achieves more efficacy using a combination of melatonin and dextromethorphan (DM; a clinically available NMDA receptor antagonist).…”
Section: Nmda Receptorsmentioning
confidence: 99%